Development of a demand feeding system for grouper juveniles – (2) tiger grouper - Tan, Nai Han; Liau, Chung Fan; Mukai, Yukinori (2012)
Demand feeding is one of the feeding methods in aquaculture. In this system, the fish turn on the switch of the feeder to get feed (Furukawa, 2001). This feeding method can improve fish growth and decrease feed losses (Azzaydi et al., 1998). The current most urgent issue facing the aquaculture industry in Malaysia is the seed production (Hussin et al., 2008). In order to develop demand feeding devices for tiger grouper seed, this study has been done to examine fish circadian rhythms and fish rearing experiment for demand feeders.